Answer:
<h2>x = 9/17</h2>
Step-by-step explanation:
3(7x-1)=4x+6 distribute
21x - 3 = 4x + 6 combine similar terms
21x - 4x = 6 + 3 simplify
17x = 9
x = 9/17
3(6x-2)+ 2(x+5)
= 3*(6x)-3*2 +2x +2*5 (distributive property)
= 18x -6 +2x +10
= (18x +2x) +(10-6)
= 20x +4
The final answer is 20x+4.
Hope this helps~
Answer:
t ≈ -2.014 or 3.647
Step-by-step explanation:
Add the opposite of the expression on the right side of the equal sign to put the equation into standard form.
4.9t² -8t -36 = 0
You can divide by 4.9 to make this a little easier to solve.
t² -(8/4.9)t -36/4.9 = 0
Now, add and subtract the square of half the x-coefficient to "complete the square."
t² -(8/4.9)t +(4/4.9)² -36/4.9 -(4/4.9)² = 0
(t -4/4.9)² -192.4/4.9² = 0 . . . . simplify
Add the constant term, then take the square root.
(t -4/4.9)² = 192.4/4.9²
t -4/4.9 = ±(√192.4)/4.9
t = (4 ± √192.4)/4.9
t ≈ {-2.014, 3.647}
Answer:
Step-by-step explanation:
If we know that D is the midpoint, then 2x + 7 = 4(x-3). Doing the algebra on that gives us
2x + 7 = 4x - 12 and
19 = 2x so
x = 9.5
It’s 2x3x3x5 because 9 isn’t prime